Wpływ koncepcji behawioralnych na współczesne systemy resocjalizacji instytucjonalnej - Ambrozik, Wiesław (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
This article presents the significant impact of behavioral concepts on how the contemporary theory and practice of social rehabilitation develops. However, it is noteworthy that even behaviorism, despite its popularity, did not manage to overcome the age-old juridical and criminological approach to prevention and social rehabilitation.